Impact of Implantation on Anxiety and Depression in Mothers of Children under Cochlear Implant - Sima Noohi; Shokoufeh Radfar; Seyed Abbas Tavallaii; Jaleh Yousefi; Mahdieh Hassan Alifard; Mohammad Ajallouyean (Tehran University of Medical Sciences, 2010)
Objective: The aim of our study is to determine the impact of cochlear implantation on anxiety anddepression in mothers of children with cochlear implant. Materials and methods: In a Cohort design, 35 mothers of deaf children with cochlear implantion admitted to the clinic of Baqiyatallah hospital during January 2008 - January 2010 were selected through systematic sampling. Information of demography, depression and anxiety are obtained from the parents by checklist and beck questionnaires, respectively. Results: Mean depression and anxiety scores in cochlear implant candidates were more than cochlear implant recipients. The difference was significant in depression and anxiety (P=0.001). Conclusion: It seems that cochlear implant use leads to decrease of depression and anxiety but still high prevalence of these complications than the normal population.